The Effect of Language Proficiency on Communication Strategy Use: A Case Study of Galician Learners of English - Ana María Fernández Dobao (Miscelánea: A Journal of English and American Studies, 2002)
This paper presents an investigation carried out in order to study the effect that language proficiency has on the use that Galician learners of English as a foreign language make of communication strategies (CS). The results obtained suggest that quantitative measures of CS instances alone cannot provide a fair picture of the use that language learners make of these devices. In analyzing CS use it is necessary to bear in mind that, in the accomplishment of the apparently same communicative tasks, different subjects set different communicative goals which directly influence their use of these strategies. On account of this, in the present study frequency and choice of CS use in a given set of tasks is related to the amount and lexical complexity of the content communicated. In this way, evidence is obtained that more proficient students use CS less frequently than lower level ones and that, in terms of CS choice, more advanced students make more frequent use of paraphrase strategies, rather than avoidance or conscious transfer strategies, than less advanced learners.